A porphyrin compound and a perovskite solar cell comprising the same

CN119569742BActive Publication Date: 2026-10-09LANZHOU UNIV
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411522562.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-29
Publication Date
2026-10-09
Estimated Expiration
2044-10-29

AI Technical Summary

Technical Problem

这种泄露可能对电池的性能稳定性造成负面影响,同时也可能导致材料的腐蚀,甚至引发环境和健康安全方面的问题

Benefits of technology

[0075] 1. This invention uses porphyrin compounds with excellent iodine adsorption properties as highly efficient iodine adsorbents, thereby improving the stability of perovskite solar cells while achieving the fixation and adsorption of iodine in the device, providing a new strategy for the preparation of efficient, stable, and environmentally friendly perovskite solar cells.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119569742B_ABST
    Figure CN119569742B_ABST
Patent Text Reader

Abstract

The application provides a porphyrin compound and a perovskite solar cell containing the same. The porphyrin compound has a structure shown in formula I or formula II. The perovskite solar cell has good iodine adsorption performance, and can effectively improve the stability of the perovskite solar cell.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a porphyrin compound and a perovskite solar cell containing the porphyrin compound. Background Technology

[0002] Perovskite solar cells have attracted much attention due to their advantages such as simple manufacturing process, low cost, and high photoelectric conversion efficiency. Currently, under laboratory conditions, the efficiency of small-area perovskite solar cells has reached an astonishing 26.7%, approaching the photoelectric conversion efficiency of silicon-based solar cells. However, the commercialization of perovskite solar cells still faces many challenges, primarily including stability and environmental safety issues.

[0003] In perovskite solar cells, iodides are commonly used as one of the photosensitive materials. However, iodine leakage may occur during long-term use. This leakage can negatively impact the cell's performance stability, lead to material corrosion, and even cause environmental and health safety issues.

[0004] Currently reported iodine adsorbent materials, such as patent documents CN110508248B, CN113070034B, and CN109569522B, have poor adsorption performance, are not stable enough in long-term use, and have more complex synthesis and processing requirements. They are not suitable for perovskite solar cells and would increase the preparation cost and engineering complexity.

[0005] Therefore, it is necessary to develop efficient adsorbents for iodine in perovskite solar cells, to provide new solutions for the preparation of efficient, stable and environmentally friendly perovskite solar cells, and to promote the industrialization of perovskite solar cells. Summary of the Invention

[0006] To address one of the aforementioned technical problems in the prior art, this invention utilizes porphyrin compounds doped into the perovskite layer of a perovskite solar cell and / or a porphyrin-containing iodine adsorption layer on the perovskite layer to efficiently adsorb and stabilize iodine, effectively solving the problem of iodine leakage in perovskite solar cells and improving the overall stability and lifespan of the device.

[0007] In a first aspect, the present invention provides a porphyrin compound having the structure shown in Formula I or Formula II:

[0008]

[0009] In Formula I, R1 to R4 may be the same or different, and each is independently selected from phenyl, hydroxyphenyl, carboxyphenyl, aminophenyl, methoxyphenyl and pyridyl, each R is independently selected from H or C1-6 alkyl, and M is selected from Fe, Mn, Co, Ni, Cu, Zn, Ti or Li;

[0010] In Formula II, R5 to R8 may be the same or different, and each is independently selected from phenyl, hydroxyphenyl, carboxyphenyl, aminophenyl, methoxyphenyl and pyridyl, and each R is independently selected from H or C1-6 alkyl.

[0011] According to some embodiments of the present invention, in Formula I and Formula II, each R is independently selected from H, methyl, ethyl, propyl, isopropyl, n-butyl, isobutyl, tert-butyl, n-pentyl, isopentyl, neopentyl, n-hexyl or isohexyl.

[0012] According to some embodiments of the present invention, in Formula I and Formula II, each R is independently selected from H or C1-4 alkyl.

[0013] According to some embodiments of the present invention, in Formula I and Formula II, each R is independently selected from H, methyl or ethyl.

[0014] According to some embodiments of the present invention, in Formula I, R1 to R4 may be the same or different, and each is independently selected from phenyl, aminophenyl and pyridyl.

[0015] According to some embodiments of the present invention, in Formula I, M is selected from Mn, Co, Ni, Cu and Zn.

[0016] According to some embodiments of the present invention, in Formula I, at least two of R1 to R4 are the same, for example, any two of R1 to R4 are the same, any three are the same, or all of R1 to R4 are the same. In some embodiments, any three of R1 to R4 are the same. In some embodiments, all of R1 to R4 are the same.

[0017] According to some embodiments of the present invention, in Formula II, R5 to R8 may be the same or different, and each is independently selected from phenyl, aminophenyl and pyridyl.

[0018] According to some embodiments of the present invention, in Formula II, at least two of R5 to R8 are the same, for example, any two of R5 to R8 are the same, any three are the same, or all of R5 to R8 are the same. In some embodiments, any three of R5 to R8 are the same. In some embodiments, all of R5 to R8 are the same.

[0019] According to some embodiments of the present invention, the porphyrin compound is selected from the group consisting of:

[0020]

[0021] A second aspect of the present invention provides a perovskite solar cell comprising a perovskite layer and optionally an iodine adsorption layer disposed on the perovskite layer, wherein the perovskite layer is doped with a compound of formula I or formula II, or the iodine adsorption layer comprises a compound of formula I or formula II, or the perovskite layer is doped with a compound of formula I or formula II, and the iodine adsorption layer comprises a compound of formula I or formula II:

[0022]

[0023] In Formula I, R1 to R4 may be the same or different, and each is independently selected from phenyl, hydroxyphenyl, carboxyphenyl, aminophenyl, methoxyphenyl and pyridyl, each R is independently selected from H or C1-6 alkyl, and M is selected from Fe, Mn, Co, Ni, Cu, Zn, Ti or Li;

[0024] In Formula II, R5 to R8 may be the same or different, and each is independently selected from phenyl, hydroxyphenyl, carboxyphenyl, aminophenyl, methoxyphenyl and pyridyl, and each R is independently selected from H or C1-6 alkyl.

[0025] According to some embodiments of the present invention, M is selected from Co, Ni, Cu, Zn, Ti, or Li.

[0026] According to some embodiments of the present invention, in Formula I and Formula II, each R is independently selected from H, methyl, ethyl, propyl, isopropyl, n-butyl, isobutyl, tert-butyl, n-pentyl, isopentyl, neopentyl, n-hexyl or isohexyl.

[0027] According to some embodiments of the present invention, in Formula I and Formula II, each R is independently selected from H or C1-4 alkyl.

[0028] According to some embodiments of the present invention, in Formula I and Formula II, each R is independently selected from H, methyl or ethyl.

[0029] According to some embodiments of the present invention, in Formula I, R1 to R4 may be the same or different, and each is independently selected from phenyl, aminophenyl and pyridyl.

[0030] According to some embodiments of the present invention, in Formula I, at least two of R1 to R4 are the same, for example, any two of R1 to R4 are the same, any three are the same, or all of R1 to R4 are the same. In some embodiments, any three of R1 to R4 are the same. In some embodiments, all of R1 to R4 are the same.

[0031] According to some embodiments of the present invention, in Formula II, R5 to R8 may be the same or different, and each is independently selected from phenyl, aminophenyl and pyridyl.

[0032] According to some embodiments of the present invention, in Formula II, at least two of R5 to R8 are the same, for example, any two of R5 to R8 are the same, any three are the same, or all of R5 to R8 are the same. In some embodiments, any three of R5 to R8 are the same. In some embodiments, all of R5 to R8 are the same.

[0033] According to some embodiments of the present invention, the porphyrin compound is selected from the group consisting of:

[0034]

[0035]

[0036] According to some preferred embodiments of the present invention, the porphyrin compound has the structure shown in the following formula:

[0037]

[0038] According to some embodiments of the present invention, the perovskite solar cell further includes a transparent electrode, an electron transport layer, a TiO2 mesoporous layer, a hole transport layer, and a metal electrode.

[0039] According to some embodiments of the present invention, the perovskite solar cell comprises, from bottom to top, a transparent electrode, an electron transport layer, a TiO2 mesoporous layer, a perovskite layer, an iodine adsorption layer, a hole transport layer, and a metal electrode.

[0040] In this invention, the conductive material used for the transparent electrode includes, but is not limited to, fluorine-doped tin oxide (FTO), indium tin oxide (ITO), or aluminum-doped zinc oxide. In some specific embodiments, the conductive material used for the transparent electrode includes fluorine-doped tin oxide (FTO).

[0041] In this invention, the materials of the electron transport layer include, but are not limited to, magnesium oxide, zinc oxide, titanium oxide, and tin oxide. In some specific embodiments, the material of the electron transport layer includes ZnO-MgO-EA. + In some specific embodiments, the material of the electron transport layer includes ZnO-MgO-EA. + And Ti(Oi-Pr)4. In some embodiments, the electron transport layer is a dense TiO2 layer.

[0042] In this invention, the material of the perovskite layer includes, but is not limited to, the organic-inorganic hybrid material ABX3, where A represents an organic amine cation (e.g., methylamine cation, formamidinium cation) and / or a cesium ion, and B represents Pb. 2+ Sn 2+Any one of the following; X represents iodine, chlorine, or bromine. In some embodiments, the material of the perovskite layer includes APbI3, where A represents an organic amine cation (e.g., methylamine cation, formamidinium cation) and / or cesium ion.

[0043] In this invention, the material of the hole transport layer includes, but is not limited to, Spiro-MeOTAD, CuSCN, etc. In some specific embodiments, the material of the hole transport layer includes Spiro-MeOTAD.

[0044] In this invention, the metal electrode can be gold (Au), silver (Ag), etc. In some specific embodiments, the metal electrode is a gold electrode.

[0045] A third aspect of the present invention provides a method for preparing the above-mentioned perovskite solar cell, comprising the following steps:

[0046] (1) An electron transport layer and a mesoporous TiO2 layer are sequentially coated on a transparent electrode, and then a perovskite precursor solution containing the porphyrin compound is coated on the mesoporous TiO2 layer to obtain a porphyrin-containing perovskite layer; optionally, a solution of the porphyrin compound is coated on the perovskite layer to obtain an iodine adsorption layer.

[0047] (2) A hole transport layer and a metal electrode are sequentially coated on the iodine adsorption layer to obtain the perovskite solar cell.

[0048] According to some embodiments of the present invention, in step (1), the perovskite precursor solution contains an iodide, which preferably includes one or more of lead iodide, methylammonium iodide, formamidine iodide, and alkali metal iodides.

[0049] According to some embodiments of the present invention, in step (1), the perovskite precursor solution includes porphyrin compound, formamidinium hydroiodate (FAI), methylamine hydrobromide (MABr), PbI2, CsI and RbI.

[0050] According to some embodiments of the present invention, in step (1), the solvent in the perovskite precursor solution includes DMF and / or DMSO.

[0051] According to some embodiments of the present invention, in step (1), the perovskite precursor solution contains lead iodide, and the porphyrin compound accounts for 0.1 to 1.0% of the molar amount of lead iodide, for example 0.1%, 0.3%, 0.5%, 0.8%, 1.0% or any value therebetween.

[0052] According to some embodiments of the present invention, in step (1), the concentration of the porphyrin compound in the porphyrin compound solution is 1-15 mg / mL, for example, 1 mg / mL, 2 mg / mL, 5 mg / mL, 8 mg / mL, 10 mg / mL, 12 mg / mL, 15 mg / mL, or any value between them. In some embodiments, in step (1), the concentration of the porphyrin compound in the porphyrin compound solution is 1-10 mg / mL.

[0053] According to some embodiments of the present invention, in step (1), the solvent in the solution of the porphyrin compound includes a haloalkane, preferably including dichloromethane and / or trichloromethane.

[0054] According to some embodiments of the present invention, in step (1), the thickness of the porphyrin-containing perovskite layer is 400-600 nm.

[0055] According to some embodiments of the present invention, in step (1), the thickness of the iodine adsorption layer is 10-30 nm.

[0056] In this invention, the transparent electrode can be obtained by laser etching of an FTO glass substrate.

[0057] In some implementations, step (1) above includes:

[0058] (S11) Ti(Oi-Pr)4 (0.15M i-PrOH solution) is coated onto the transparent electrode and annealed at high temperature (e.g. 450℃-550℃) (e.g. 20-40 minutes) to obtain a dense TiO2 layer;

[0059] (S12) The above substrate is placed in a pre-prepared TiCl4 solution, heated, dried, and then coated with mesoporous TiO2 slurry on the dense TiO2 layer. The substrate is then annealed at high temperature (e.g., 450℃-550℃) (e.g., 20-40 minutes) to obtain a mesoporous TiO2 layer.

[0060] (S13) A perovskite precursor solution containing the porphyrin compound is coated onto the mesoporous TiO2 layer to obtain a porphyrin-containing perovskite layer; and optionally...

[0061] (S14) A solution of the porphyrin compound is coated onto the perovskite layer to obtain an iodine adsorption layer.

[0062] In some embodiments, in step (S11), the concentration of the Ti(Oi-Pr)4 solution is 0.1-0.2M, for example, 0.15M. In some embodiments, in step (S11), the coating rotation speed is 2500-3000 rpm; the time is 20-40 s.

[0063] In some embodiments, in step (S12), the concentration of the TiCl4 solution is 0.5-1.5M, preferably 1M. In some embodiments, in step (S12), the heating temperature is 60-80°C, and the heating time is 8-15 minutes. In some embodiments, in step (S12), the mesoporous TiO2 slurry comprises an isopropanol solution of TiO2, preferably, the mass ratio of TiO2 to isopropanol is 1:(5-10). In some embodiments, in step (S12), the coating method is spin coating. The spin coating speed is 4500-5500 rpm; the time is 20-40 s.

[0064] Thirdly, the present invention provides compounds of Formula I or Formula II as iodine adsorbents and / or for use in perovskite solar cells:

[0065]

[0066] In Formula I, R1 to R4 may be the same or different, and each is independently selected from phenyl, hydroxyphenyl, carboxyphenyl, aminophenyl, methoxyphenyl and pyridyl, R is selected from H or C1-6 alkyl, and M is selected from Co, Ni, Cu, Zn, Ti or Li;

[0067] In Formula II, R5 to R8 may be the same or different, and each is independently selected from phenyl, hydroxyphenyl, carboxyphenyl, aminophenyl, methoxyphenyl and pyridyl, and R is selected from H or C1-6 alkyl.

[0068] According to some embodiments of the present invention, in Formula I, R1 to R4 may be the same or different, and each is independently selected from phenyl, aminophenyl and pyridyl.

[0069] According to some embodiments of the present invention, in Formula I, at least two of R1 to R4 are the same, for example, any two of R1 to R4 are the same, any three are the same, or all of R1 to R4 are the same. In some embodiments, any three of R1 to R4 are the same. In some embodiments, all of R1 to R4 are the same.

[0070] According to some embodiments of the present invention, in Formula II, R5 to R8 may be the same or different, and each is independently selected from phenyl, aminophenyl and pyridyl.

[0071] According to some embodiments of the present invention, in Formula II, at least two of R5 to R8 are the same, for example, any two of R5 to R8 are the same, any three are the same, or all of R5 to R8 are the same. In some embodiments, any three of R5 to R8 are the same. In some embodiments, all of R5 to R8 are the same.

[0072] According to some embodiments of the present invention, the porphyrin compound is selected from the group consisting of:

[0073]

[0074] Compared with the prior art, the present invention has the following beneficial effects:

[0075] 1. This invention uses porphyrin compounds with excellent iodine adsorption properties as highly efficient iodine adsorbents, thereby improving the stability of perovskite solar cells while achieving the fixation and adsorption of iodine in the device, providing a new strategy for the preparation of efficient, stable, and environmentally friendly perovskite solar cells.

[0076] 2. In the structure of perovskite solar cells, the perovskite layer contains photosensitive materials containing iodides, which are easily affected by external factors in the natural environment, leading to instability and dissociation of the crystal structure, ultimately causing a decline in cell performance. This application adopts a post-processing method in the perovskite solar cell fabrication process, that is, after the perovskite layer is crystallized, a layer of porphyrin compound material is coated on it, thereby fixing and adsorbing the iodine element in the perovskite layer to improve the structural stability of the perovskite solar cell. Attached Figure Description

[0077] Figure 1 The iodine adsorption effect of tetrapyridinephenylporphyrin tested in Example 1 of this application is shown.

[0078] Figure 2 The iodine adsorption effect of tetraaminophenylporphyrin tested in Example 1 of this application is shown.

[0079] Figure 3 The iodine adsorption effect of diaminophenylporphyrin tested in Example 1 of this application is shown.

[0080] Figure 4 The iodine adsorption effect of monoaminophenylporphyrin tested in Example 1 of this application is shown.

[0081] Figure 5 The iodine adsorption effect of the porphyrin cobalt complex tested in Example 1 of this application is shown.

[0082] Figure 6 The iodine adsorption effect of the porphyrin nickel complex tested in Example 1 of this application is shown.

[0083] Figure 7 The iodine adsorption effect of the porphyrin copper complex tested in Example 1 of this application is shown.

[0084] Figure 8 The iodine adsorption effect of the zinc porphyrin complex tested in Example 1 of this application is shown.

[0085] Figure 9The iodine adsorption effect of the octaethyl monoaminophenyl nickel porphyrin complex tested in Example 1 of this application is shown.

[0086] Figure 10 The photoelectric conversion efficiency of the perovskite solar cell prepared in Example 2 of the present invention is shown.

[0087] Figure 11 The photoelectric conversion efficiency of the perovskite solar cell prepared in Example 3 of the present invention is shown.

[0088] Figure 12 The photoelectric conversion efficiency of the perovskite solar cell prepared in Example 4 of the present invention is shown.

[0089] Figure 13 The photoelectric conversion efficiency of the perovskite solar cell prepared in Example 5 of the present invention is shown.

[0090] Figure 14 The photoelectric conversion efficiency of the perovskite solar cell prepared in Example 6 of the present invention is shown.

[0091] Figure 15 The light stability test results of the perovskite solar cells prepared in Examples 2 and 5 of the present invention are shown.

[0092] Figure 16 The results of iodine adsorption performance tests on perovskite films before and after CuP treatment are shown.

[0093] Figure 17 The UV-Vis spectra of the perovskite films before and after CuP treatment in the iodine adsorption experiment are shown. Detailed Implementation

[0094] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to embodiments and accompanying drawings. The specific embodiments described herein are for illustrative purposes only and are not intended to limit the scope of the invention in any way.

[0095] Unless otherwise specified, all reagents used in the following experiments of this invention are commercially available products or reagents prepared according to conventional methods. Unless otherwise specified, all methods used in the experiments are conventional experimental methods. Unless otherwise specified, all instruments used in the experiments are commercially available.

[0096] The tetrapyridinephenylporphyrin, tetraaminophenylporphyrin, and diaminophenylporphyrin used in this invention are obtained through commercial channels.

[0097] The reagents used in the synthesis of meso-tetraphenylporphyrin, N,N-dimethylformamide, dimethyl sulfoxide, metal acetates, 3,4-diethylpyrrole, and benzaldehyde were purchased from Bailingwei Technology Co., Ltd.; solvents such as diethyl ether and acetic acid were purchased from Sichuan Kelong Scientific Co., Ltd.; trifluoroacetic acid was purchased from TCI Chemical Industry Development Co., Ltd.; and iodine was purchased from Sigma-Aldrich. All materials used in the examples were obtained directly from or synthesized from the above materials.

[0098] The FTO conductive glass, laser etching machine (Wuhan Junwei Technology JW-20W-KS), spin coater (Wuhan Junwei Technology JW-A5), sunlight simulator (Newport), vacuum coating machine (Micro-Nano Vacuum VZZ-300), iodine (Sigma-Aldrich), zinc acetate (Bailingwei Technology Co., Ltd.), magnesium acetate (Bailingwei Technology Co., Ltd.), etc. are all commercially available reagents and are used directly without any additional processing.

[0099] Synthesis Example 1: Synthesis of Monoaminophenylporphyrin (Por)

[0100] The synthesis route is as follows:

[0101]

[0102] Tetraphenylporphyrin was added to 10 mL of TFA, followed by slow addition of sodium nitrite at a 1 / 1.8 equivalent. The mixture was stirred at room temperature for 3 min, the reaction was quenched with water, and extracted with dichloromethane. The organic layer was washed with a saturated aqueous solution of NaHCO3, and the solvent was evaporated under vacuum. After dichloromethane evaporation, the product was dispersed in concentrated hydrochloric acid (10 mL), and 6 equivalents of stannous chloride were added. The reaction mixture was heated to 60 °C for 6 h, cooled to room temperature, and the solid residue was collected, dissolved in dichloromethane, and washed until pH = 8. The organic layer was concentrated, dried, and purified by silica gel column chromatography, eluting with dichloromethane. The solvent was evaporated under vacuum to give compound Por.

[0103] Synthesis Example 2: Synthesis of Monoaminophenylporphyrin Metal Complexes

[0104] The synthesis route is as follows:

[0105]

[0106] The synthesis steps are as follows:

[0107] Monoaminophenylporphyrin was dissolved in chloroform (100 mL), and excess methanol (10 mL) solutions of Co(OAc)₂, Cu(OAc)₂, and Zn(OAc)₂ were added, respectively. The mixture was refluxed at 65 °C for 4 hours. The reaction was monitored under UV light. After the reaction was completed, the mixture was extracted three times with water, and the solvent was removed under reduced pressure to obtain monoaminophenylporphyrin cobalt complex CoP, monoaminophenylporphyrin copper complex CuP, and monoaminophenylporphyrin zinc complex ZnP, respectively.

[0108] Monoaminophenylporphyrin was dissolved in DMF, and excess Ni(OAc)₂·4H₂O was added. The mixture was refluxed at 110 °C for 4 hours. The reaction was monitored under UV light. After the reaction was complete, the mixture was extracted three times with water, and the solvent was removed under reduced pressure to obtain the monoaminophenylporphyrin nickel complex NiP.

[0109] Synthesis Example 3: Synthesis of Octaethylmonoaminophenylnickel porphyrin (NiOP)

[0110]

[0111] 3,4-Diethylpyrrole (360 μL) and benzaldehyde (268 μL) were added separately to 125 mL of acetic acid. The mixture was refluxed for 2 hours. After the reaction was complete, the solvent was removed. The residue was dissolved in dichloromethane and washed with saturated sodium bicarbonate until the washing solution was alkaline. The organic phase was concentrated and purified by silica gel column chromatography using dichloromethane / methanol (1:2%, v / v) as the eluent. Recrystallization from the eluent gave a green solid, and 2,3,7,8,12,13,17,18-octaethyl-5,10,15,20-tetraphenylporphyrin (H2OETPP) was synthesized.

[0112] 1.4 equivalents of NaNO2 were slowly added to a concentrated TFA solution of H2OETPP and reacted for 3 minutes, mainly producing mononitroporphyrins. The reaction was quenched with water after completion. The solvent was removed, and then the nitroporphyrins were reduced to the corresponding aminoporphyrins using excess stannous chloride dihydrate in HCl solution. The resulting aminoporphyrins were separated by silica gel chromatography using dichloromethane / methanol as the eluent. The eluent was concentrated to obtain a green solid, octaethylmonophenylporphyrin (Por1).

[0113] Following the method of Synthesis Example 2, "monoaminophenylporphyrin" was replaced with "octaethylmonoaminophenylporphyrin (Por1)" to obtain octaethylmonoaminophenylnickelporphyrin (NiOP).

[0114] Example 1: Test of iodine adsorption effect of porphyrin

[0115] Tetrapyridinephenylporphyrin, tetraaminophenylporphyrin, diaminophenylporphyrin, monoaminophenylporphyrin, and the five porphyrin metal complexes CoP, CuP, ZnP, NiP, and NiOP obtained in the above synthesis examples 1-3 were used as adsorbents to test the iodine adsorption capacity. Static adsorption tests were used to assess the adsorption capacity of porphyrins for I2 vapor to evaluate the adsorption capacity of different porphyrins for I2.

[0116] Two powdered samples, porphyrin and iodine, were placed in a sealed bottle and then heated at 75°C. The mass change of porphyrin was measured at intervals, and the results are as follows: Figures 1 to 9 As shown, the iodine adsorption capacity of porphyrin increases with time. From Figures 1 to 9 Furthermore, it was observed that several porphyrin compounds exhibited significant adsorption performance for iodine, with tetrapyridylporphyrin showing the best adsorption effect, reaching an adsorption capacity of 6.48 g / g. In addition, tetraaminophenylporphyrin and monoaminophenyl copper porphyrin also showed good iodine adsorption effects, with adsorption capacities of 6.25 g / g and 5.87 g / g, respectively. Considering solubility and other issues, monoaminophenyl copper porphyrin (CuP) was selected as a passivating agent for perovskite solar cells.

[0117] Example 2: Fabrication of perovskite solar cells

[0118] The FTO glass was etched using a laser etching machine to obtain the electrode pattern. The substrate was then ultrasonically washed sequentially with acetone, water, and ethanol for 10 minutes each. After drying, the glass substrate was treated with UV ozone for 15 minutes. Ti(Oi-Pr)4 (0.15M i-PrOH solution) was then spin-coated onto the FTO glass substrate (2800 rpm, 25 s), followed by annealing at 500°C for 30 minutes to complete the preparation of the dense layer. After cooling to room temperature, the substrate was immersed in a 1M TiCl4 solution at 70°C and heated for 12 minutes. After drying, mesoporous TiO2 (slurry: isopropanol 1:8, mass ratio) was spin-coated at 5000 rpm for 25 s, followed by annealing at 500°C for 30 minutes. 167.03 mg FAI, 22.28 mg MABr, and 599.31 mg PbI₂ were dissolved in a mixed solution of DMF and DMSO (743 μL: 186 μL). Then, 47.8 μL (1.5 M) of CsI in DMSO solution and 46.9 μL (1.5 M) of RbI in DMSO solution were added to prepare a perovskite precursor solution. The perovskite precursor solution was spin-coated in a nitrogen glove box (800-4000 rpm, 10-30 s), and after annealing, a dense perovskite film with a thickness of 500 nm was obtained. The hole transport layer Spiro-OMeTAD was spin-coated at 4000 rpm. Finally, 80 nm of gold was deposited using a vacuum deposition apparatus, and the cell efficiency was tested under a solar simulator.

[0119] Example 3: Fabrication of perovskite solar cells doped with monoamine phenyl copper porphyrin (CuP)

[0120] The preparation of the perovskite precursor solution in this embodiment is the same as in Example 2.

[0121] The FTO glass was etched using a laser etching machine to obtain the electrode pattern. The substrate was then ultrasonically washed sequentially with acetone, water, and ethanol for 10 minutes each. After drying, the glass substrate was treated with UV ozone for 15 minutes. Ti(Oi-Pr)4 (0.15M i-PrOH solution) was then spin-coated onto the FTO glass substrate (2800 rpm, 25 s), followed by annealing at 500°C for 30 minutes to complete the preparation of the dense layer. After cooling to room temperature, the substrate was immersed in a 1M TiCl4 solution at 70°C and heated for 12 minutes. After drying, mesoporous TiO2 (slurry: isopropanol 1:8, mass ratio) was spin-coated at 5000 rpm for 25 s, followed by annealing at 500°C for 30 minutes. 0.5% CuP was added to the above perovskite precursor solution (0.5% molar ratio relative to PbI2), and spin-coating was performed in a nitrogen glove box (800-4000 rpm, 10-30 s). After annealing, a dense perovskite film with a thickness of 500 nm was obtained. The hole transport layer Spiro-OMeTAD was spin-coated at 4000 rpm. Finally, 80 nm of gold was deposited using a vacuum deposition apparatus, and the cell efficiency was tested under a solar simulator.

[0122] Example 4

[0123] The difference from Example 3 is that after the dense perovskite film is prepared, a layer of CuP in chloroform solution (with a concentration of 1 mg / mL of monoaminophenylporphyrin copper) is spin-coated (4000 rpm, 25 s) onto the perovskite film to obtain an iodine adsorption layer; then a hole transport layer is spin-coated.

[0124] Example 5

[0125] The difference from Example 3 is that after the dense perovskite film is prepared, a layer of CuP in chloroform solution (with a concentration of 5 mg / mL of monoaminophenylporphyrin copper) is spin-coated (4000 rpm, 25 s) onto the perovskite film to obtain an iodine adsorption layer with a thickness of about 20 nm; then a hole transport layer is spin-coated.

[0126] Example 6

[0127] The difference from Example 3 is that after the dense perovskite film is prepared, a layer of CuP in chloroform solution (with a concentration of 10 mg / mL of monoaminophenylporphyrin copper) is spin-coated (4000 rpm, 25 s) onto the perovskite film to obtain an iodine adsorption layer; then a hole transport layer is spin-coated.

[0128] Experiment 1: Photovoltaic Conversion Efficiency Test of Perovskite Solar Cells

[0129] The photoelectric conversion efficiency of the perovskite solar cells prepared in Examples 2-6 was tested using a device (Newport) equipped with a Keithley 2400 source meter and an LSH-7320ABA LED lamp simulator. Current-voltage (IV) curves were measured. Prior to testing, the light intensity was calibrated to 100 mW·cm using a standard silicon cell. -2 This refers to AM 1.5G sunlight conditions. The results are as follows: Figure 10-14 As shown, the perovskite solar cell prepared in Example 3 exhibits the best photoelectric conversion efficiency.

[0130] The control perovskite solar cell in Example 2 had a cell efficiency of only 21.18% when tested under a solar simulator. Figure 10 ).

[0131] Example 3: A perovskite solar cell prepared by doping 0.5% CuP into perovskite showed an efficiency of 22.18% when tested under a solar simulator. Figure 11 ).

[0132] Example 4: A perovskite solar cell prepared by spin-coating a perovskite layer with 1 mg / mL CuP showed an efficiency of 21.76% under a solar simulator. Figure 12 ).

[0133] Example 5: A perovskite solar cell prepared by spin-coating a perovskite layer with 5 mg / mL CuP showed an efficiency of 22.06% under a solar simulator. Figure 13 ).

[0134] Example 6: A perovskite solar cell prepared by spin-coating 10 mg / mL CuP onto a perovskite layer showed an efficiency of 20.07% when tested under a solar simulator. Figure 14 ).

[0135] Experiment 2: Light Stability Test of Perovskite Solar Cells

[0136] In the illumination test, the perovskite solar cell prepared by post-treatment of the perovskite layer with a 5 mg / mL monoaminophenyl copper porphyrin solution in Example 5 also exhibited excellent stability. Figure 15 As shown, after 20 hours of light stability testing, the battery structure of the device without porphyrin metal complex treatment was completely destroyed and decomposed, while the device in Example 5 treated with porphyrin metal complex CuP still maintained a better morphology.

[0137] Experiment 3: Stability and Iodine Adsorption Performance Testing of Perovskite Solar Cell Devices

[0138] The adsorption capacity of CuP for released iodine in perovskite films was evaluated using a conventional iodine-starch colorimetric reaction. Perovskite films, before and after CuP treatment, were placed in glass tubes containing 1 mL of starch aqueous solution at the bottom. The glass tubes were continuously irradiated under AM 1.5G light. After one hour of irradiation, the starch aqueous solution in the control device changed from colorless to purple, becoming clearly visible to the naked eye. In contrast, under the same irradiation conditions, the starch aqueous solution in the CuP-based device remained colorless. Figure 16 The results show that the introduced CuP can effectively suppress the release of iodine from the device, indicating that the CuP-treated device has excellent iodine adsorption performance.

[0139] Because I2 and the movable I - The ions readily react to produce triiodide ions (I3) in water. - Therefore, the starch solution in the glass tube was replaced with water to further quantify the iodine vapor emissions from the equipment. Figure 17 As shown, after 20 hours of irradiation, the release of iodine was assessed using UV-Vis spectroscopy. The results indicated that the control group showed significant I3 release at 351 nm. - Absorption peaks were observed in CuP-treated perovskite solar cells, while the absorption peaks in CuP-treated samples were almost negligible. A significant reduction in iodine release was observed in CuP-treated perovskite solar cells, demonstrating the effectiveness of this treatment strategy.

[0140] The technical solutions of the present invention are not limited to the specific embodiments described above. Any technical modifications made in accordance with the technical solutions of the present invention fall within the protection scope of the present invention.

Claims

1. A perovskite solar cell comprising a perovskite layer and an iodine adsorption layer disposed on the perovskite layer, wherein the iodine adsorption layer contains a porphyrin compound, or The perovskite layer is doped with porphyrin compounds, and the iodine adsorption layer contains porphyrin compounds; The porphyrin compound is selected from the group consisting of the following compounds: 。 2. The perovskite solar cell according to claim 1, characterized in that, The porphyrin compound has the structure shown in the following formula: 。 3. The perovskite solar cell according to any one of claims 1-2, characterized in that, The perovskite solar cell also includes a transparent electrode, an electron transport layer, a hole transport layer, and a metal electrode.

4. The perovskite solar cell according to claim 3, characterized in that, The perovskite solar cell comprises, from bottom to top, a transparent electrode, an electron transport layer, a TiO2 mesoporous layer, a perovskite layer, an iodine adsorption layer, a hole transport layer, and a metal electrode.

5. A method for preparing a perovskite solar cell according to any one of claims 1-4, comprising the following steps: (1) An electron transport layer and a mesoporous TiO2 layer are sequentially coated on a transparent electrode, and then a perovskite precursor solution containing the porphyrin compound is coated on the mesoporous TiO2 layer to obtain a porphyrin-containing perovskite layer. A solution of the porphyrin compound was coated onto the perovskite layer to obtain an iodine adsorption layer; (2) A hole transport layer and a metal electrode are sequentially coated on the iodine adsorption layer to obtain the perovskite solar cell.

6. The method according to claim 5, characterized in that, In step (1), the perovskite precursor solution contains iodide; and / or, In step (1), the perovskite precursor solution comprises a porphyrin compound, formamidinium hydroiodate, methylamine hydrobromide, PbI₂, CsI, and RbI; and / or, In step (1), the perovskite precursor solution contains lead iodide, and the porphyrin compound accounts for 0.1~1.0% of the molar amount of lead iodide; and / or, In step (1), the concentration of the porphyrin compound in the solution is 1-15 mg / mL; In step (1), the solvent in the solution of the porphyrin compound includes a haloalkane; and / or, In step (1), the thickness of the porphyrin-containing perovskite layer is 400-600 nm; and / or, In step (1), the thickness of the iodine adsorption layer is 10-30 nm.

7. The method according to claim 6, characterized in that, The iodide includes one or more of lead iodide, methylammonium iodide, and methylammonium iodide; and / or, In step (1), the perovskite precursor solution contains lead iodide, and the porphyrin compound accounts for 0.3-0.8% of the molar amount of lead iodide; and / or, In step (1), the solvent in the solution of the porphyrin compound includes dichloromethane and / or trichloromethane.

8. Applications of porphyrin compounds as iodine adsorbents, among which, The porphyrin compound is selected from the group consisting of the following compounds: 。 9. The application according to claim 8, characterized in that, The applications include the use of the porphyrin compound as an iodine adsorbent in perovskite solar cells.

Citation Information

Patent Citations

  • An iodine adsorbent material, its preparation method and application

    CN109569522B

  • An iodine adsorbent material and its preparation method

    CN110508248B

  • An iodine adsorbent material and its preparation method

    CN113070034B

  • Method for efficiently and stably preparing large-area perovskite solar cell based on porphyrin doping

    CN109860394A

  • Method for preparing perovskite solar cell from porphyrin complex self-assembled supramolecules

    CN113754893A